IMPLEMENTASI METODE PROTOTYPE DALAM PERANCANGAN APLIKASI INVENTORY DAN CLOSSING KEUANGAN BERBASIS ANDROID MENGGUNAKAN MOBILE PROGAMMING DI CAFE SUDUT SEDJENAK - Nurwidodo Nurwidodo (JUPIK : Jurnal Penelitian Ilmu komputer, 2023)
Sedjenak Corner is a cafe engaged in the field of food and beverages. The problem that occurs in the current running system is the management of incoming and outgoing goods data or inventory and closing which contains a recap of sales data for 1 day which will be sent to the owner, only recorded on a piece of paper then photographed and sent to the owner, so that it is difficult to calculating goods and financial calculations. Sometimes stock information does not match the existing inventory stock and financial reports do not match the number of existing sales. The purpose of this research is to create an Inventory and Financial Closing Application that can manage incoming and outgoing stock, ordering data, and accurate financial reports using the prototype method. The application that will be built will be able to manage incoming and outgoing goods data, ordering data and financial reports that can be done online.